2023
DOI: 10.1038/s41598-023-29815-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk perception and gratitude mediate the negative relationship between COVID-19 management satisfaction and public anxiety

Abstract: In this study, we explored whether satisfaction with government management, perception of risk, and gratitude influenced public anxiety during the COVID-19 pandemic in China. Using a cross-sectional, anonymous and confidential online survey, a nationwide sample of Chinese adults (N = 876) was targeted between March 25–March 30, 2020, a period in which newly confirmed cases significantly declined in China. The anxiety level was decreased as compared to that assessed during the peak period. Multiple parallel med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…Simulation studies have shown that under certain assumptions (discussed in a later section), DDA-based tests can correctly select the causal directionality in competing models (e.g., x → y vs. y → x ; Pornprasertmanit & Little, 2012; Rosenström et al, 2023; von Eye & DeShon, 2012; Wiedermann & von Eye, 2015a). More recently, we have observed an increasing number of DDA applications in the field of psychological studies (e.g., Akkuş & Peker, 2022; Chew et al, 2020; Dierckx et al, 2022; Li et al, 2022; Mei et al, 2023; Wiedermann et al, 2020).…”
mentioning
confidence: 99%
“…Simulation studies have shown that under certain assumptions (discussed in a later section), DDA-based tests can correctly select the causal directionality in competing models (e.g., x → y vs. y → x ; Pornprasertmanit & Little, 2012; Rosenström et al, 2023; von Eye & DeShon, 2012; Wiedermann & von Eye, 2015a). More recently, we have observed an increasing number of DDA applications in the field of psychological studies (e.g., Akkuş & Peker, 2022; Chew et al, 2020; Dierckx et al, 2022; Li et al, 2022; Mei et al, 2023; Wiedermann et al, 2020).…”
mentioning
confidence: 99%